Being acknowledged by others and bracketing negative thoughts and feelings: Frail older people's narrations of how existential loneliness is eased. (7th November 2018) - Sjöberg, Marina; Edberg, Anna‐Karin; Rasmussen, Birgit H.; Beck, Ingela
Abstract: Aims and objectives: The aim of this study was to describe how EL was eased, as narrated by frail older people. Background: Existential loneliness (EL) is an unavoidable part of the human condition. It is a complex phenomenon that has been described as disconnection from life. If EL is acknowledged in the care of older people, the experience of EL can be reduced. Design: In this qualitative study, we used an exploratory and descriptive design. Methods: The study was based on 22 narrative interviews with frail older people, 76 to 101 years old, who were receiving long‐term care and services. We analysed the data using conventional content analysis. Results: Being acknowledged by others, that is, being the focus of others' concern, eased the experience of EL, as did encountering intimacy and having meaningful exchanges of thoughts and feelings. Further, EL was pushed into the background and eased when participants could bracket negative thoughts and feelings, that is, when they could adjust and accept the present situation, view life in the rear‐view mirror, be in contact with spiritual dimensions and withdraw and distract themselves. Conclusion: Existential loneliness can be eased by experiencing meaningful togetherness with others and oneself when something else comes to the forefront, pushing EL to the background. Frail older peoples' opportunities to ease EL may be facilitated by health care staff (HCS) providing person‐centred care and create possibilities for solitary time and meaningful togetherness. Implications for practice: If frail older people's ongoing processes of adjusting and accepting their situation are understood and confirmed by people in their environment, for example, by nurses, family and friends, the experience of living a meaningful life can be supported, which, in turn, can ease EL.